Strategi Komunikasi Persuasif Penyidik Tindak Pidana Umum Kepolisian Resor Aceh Tengah Dalam Menginterogasi Para Saksi - Kotawarmi, Win; Surya, Achmad; Fachri, Husni (Universitas Gajah Putih, 2022)
The police in handling criminal cases are certainly faced with a choice between legal certainty with justice and expediency. The existence of witnesses in a criminal justice process starting from the stage of investigation, prosecution to trial in court in order to provide information in order to reveal the facts of the occurrence of a crime. The importance of communication is a part that cannot be replaced in writing or otherwise, because communication has functions that include, to inform, namely to provide information given by witnesses to investigators for the completeness of the investigation. The purpose of the study was to determine the persuasive communication strategy of members of the Central Aceh District Police in interrogating witnesses, and to find out what factors hindered the persuasive communication of members of the Central Aceh District Police in interrogating witnesses. This research is a type of qualitative descriptive research, namely research that has descriptive results in the form of words and writings from informants studied by researchers, while the approach used in this study is a descriptive approach where researchers look for facts, phenomena about the communication strategy of district resort police investigators. Aceh is in the process of interrogating a suspect in the crime of burning a house. Sources of data used are primary data obtained directly in the field and secondary data obtained from literature or library materials. The results showed that the communication strategy used by the investigator in the witness interrogation process was in accordance with the established SOP, and the interrogation communication strategy used was persuasive communication and interpersonal communication. Persuasive communication is carried out using clear, firm and straightforward language. In addition to persuasive communication techniques, interpersonal communication techniques are also an option for investigators when interrogating witnesses humanely by respecting human values. The factors that hinder persuasive communication by members of the Aceh Resort Police are in interrogating the witnesses, the statements from witnesses are always different, even seem to change and answering questions from investigators is often convoluted making it difficult for investigators to get information from witnesses, and witnesses are not present in the process of examining witnesses at the investigation stage.